Analisis Strategi Pengelolaan Sampah di Kota Cimahi dengan Kerangka SOAR - Muflihah, Lilih; Widyarsana, I Made Wahyu (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Population growth and metropolitan activity in Cimahi City, with a population of 598,698 residents in 2024, and with a waste composition dominated by organic materials, have heightened the need for a more effective waste management system. Sarimukti Landfill, which serves as the regional disposal site for Greater Bandung, has exceeded its capacity, requiring compliance with disposal capacity limits within its service coverage. Given the limited land availability and high population density, optimizing existing waste management facilities has become the most relevant and feasible strategy. This study aims to formulate sustainable waste management strategies for Cimahi City by identifying strategic factors using the SOAR framework. Data were collected through semi-structured interviews and direct observations with stakeholders involved in waste management in Cimahi City. The SOAR approach was selected to explore strengths, opportunities, aspirations, and expected results, thereby producing a strategic mapping that emphasizes stakeholder collaboration. Based on the SOAR analysis, the Strength–Aspirations (SA) strategy demonstrates the greatest implementation potential, comprising efforts to strengthen waste-sorting literacy and practices, develop standardized SOPs, enhance inter-agency coordination, innovate volume-based financing schemes and digital service channels, and reorganize operational systems toward sustainability.